The practice and implications of functional analysis (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
This article explores the meaning of functional analysis from the typical situation of the Skinner Box in the operant animal laboratory to the clinical setting. It proposes a reflection on multiple ways of doing a functional analysis and about their paradigmatic and practical implications. Functional analysis as practiced within Applied Behavior Analysis bears with it the methodological safeguards inherited from Experimental Analysis. Functional analysis as practiced within Clinical Behavior Analysis pushed the same experimental way of thinking a step beyond these safeguards, taking seriously Skinner’s consideration that the subject controls the behavior of the analyst as much as the analyst controls the behavior of the subject. Both ways of making a functional analysis are valid, depending on the purpose and context of the analysis, although Clinical Behavior Analysis confronted us in a more acute way with the epistemological implications of functional analysis: the contextualistic worldview, the axiom of functional primacy and the recursive nature of the analysis.